Influence of Gender and Level of Education of Farmers on Sugarcane Productivity in the Visayas, Philippines: A Factual Phenomenon - Paulino A. Oñal, Jr.; Paulino Miguel M. Oñal (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Agriculture is the backbone of an economy. In the Philippines, sugarcane farming is a major dollar industry that contributes an average income of Php 70 billion per year. The study aims to examine the influence of farmers’ gender and the level of education on sugarcane productivity in the Philippines. The descriptive-correlation method was employed in the study. The instrument used was a validated survey questionnaire with a Cronbach’s alpha of 0.84. The 320 sugarcane farmers were randomly identified at the seven locations in the Visayas area of the Philippines. Results indicate that the majority of the farmers are male (69.7%), secondary level (47.2%), with a low average production of <49 TC/ha. (53.9%). Analysis of variance (ANOVA) implied that there’s a significant difference in the production of sugarcane among the different locations in the Philippines (alpha = 0.05). Furthermore, results implied that farmers' gender and their level of education significantly influence the production (alpha = 0.01). Relatively, the farmer's gender and their level of education strongly correlate with production (alpha = 0.01). Overall, the results implied that farmers’ gender and level of education have a direct contribution to production. Hence, the government should play a vital role in improving the agricultural educational system. The budget for education should be increased, and more scholarship be made available, especially for students who will be taking courses in the agriculture field. More seminars and updates for aged and female farmers should be designed by the government.